2019
DOI: 10.3390/insects10070187
|View full text |Cite
|
Sign up to set email alerts
|

The Thermoregulatory Behavior of Nectar Foraging Polistine Wasps (Polistes dominula and Polistes gallicus) in Different Climate Conditions

Abstract: Polistine wasps collect nectar for their energetic demand and for the provision of the brood. They are mainly ectothermic during different behavioral tasks. We investigated the body temperature of two species living in differing habitats and climate regions, in order to reveal the environmental influence on their thermoregulatory behavior. The species were Polistes dominula in the temperate climate of Central Europe, and Polistes gallicus in the warm Mediterranean climate of Southern Europe. The wasp’s body te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 23 publications
0
9
0
Order By: Relevance
“…Ref. 69,70] can facilitate the measurement of reflectance and its effects on rates of temperature change of a large number of insects (intra-specifically and inter-specifically) through space and time, and therefore enhance our understanding of evolutionary relationships between color and climate at fine scales. A combination of longterm field surveys (or museum records), genetic data, laboratory controlled experiments and insect field performance provides great promise to understand the value of color variation as a mediator of climate change effects on insects.…”
Section: Discussionmentioning
confidence: 99%
“…Ref. 69,70] can facilitate the measurement of reflectance and its effects on rates of temperature change of a large number of insects (intra-specifically and inter-specifically) through space and time, and therefore enhance our understanding of evolutionary relationships between color and climate at fine scales. A combination of longterm field surveys (or museum records), genetic data, laboratory controlled experiments and insect field performance provides great promise to understand the value of color variation as a mediator of climate change effects on insects.…”
Section: Discussionmentioning
confidence: 99%
“…The number of cells per nest and number of adult wasps were recorded before and after the experiment. Research has found temperature to have an important effect on P. dominula nest growth (Höcherl and Tautz 2015) and foraging (Weiner et al 2011), with wasps failing to forage for food at temperatures below 20°C (Kovac et al 2019). To compare temperatures between habitats, HOBO Pendant UA-001-08 temperature data loggers were placed within each site on the nest boxes, logging the temperature every 10 min.…”
Section: Translocation Of P Dominula Nestsmentioning
confidence: 99%
“…The number of cells per nest and the number of adult wasps were recorded before and after the experiment. Research has found temperature to have an important effect on Polistes nest growth (Höcherl & Tautz, 2015) and foraging (Weiner et al, 2011), with wasps failing to forage for food at temperatures below 20°C (Kovac et al, 2019). To compare temperatures between habitats, HOBO Pendant® UA-001-08 temperature data loggers were placed within each site on the nest boxes.…”
Section: Translocation Of P Dominula Nestsmentioning
confidence: 99%